Early Dyskinesias in Parkinson’s Disease Patients With Parkin Mutation: A Primary Corticostriatal Synaptopathy? - Sassone, Jenny; Valtorta, Flavia; Ciammola, Andrea (Frontiers in Neuroscience, 2019)
Mutations in the PARKIN gene cause early-onset Parkinson’s disease (PD). Despite the high proportion of still missing phenotyping data in the literature devoted to early-onset PD, studies suggest that, as compared with late-onset PD, PARKIN patients show dystonia at onset and extremely dose-sensitive levodopa-induced dyskinesia (LID). What pathophysiological mechanisms underpin such early and atypical dyskinesia in patients with PARKIN mutations? Though the precise mechanisms underlying dystonia and LID are still unclear, evidence suggests that hyperkinetic disorders in PD are a behavioral expression of maladaptive functional and morphological changes at corticostriatal synapses induced by long-term dopamine (DA) depletion. However, since the dyskinesia in PARKIN patients can also be present at onset, other mechanisms beside the well-established DA depletion may play a role in the development of dyskinesia in these patients. Because cortical and striatal neurons express parkin protein, and parkin modulates the function of ionotropic glutamatergic receptors (iGluRs), an intriguing explanation may rest on the potential role of parkin in directly controlling the glutamatergic corticostriatal synapse transmission. We discuss the novel theory that loss of parkin function can dysregulate transmission at the corticostriatal synapses where they cause early maladaptive changes that co-occur with the changes stemming from DA loss. This hypothesis suggests an early striatal synaptopathy; it could lay the groundwork for pharmacological treatment of dyskinesias and LID in patients with PARKIN mutations.